Differential Effects of Ethical Education, Physical Hatha Yoga, and Mantra Meditation on Well-Being and Stress in Healthy Participants—An Experimental Single-Case Study - Matko, Karin; Sedlmeier, Peter; Bringmann, Holger C. (Frontiers in Psychology, 2021)
Traditionally, yoga is a multicomponent practice consisting of postures, breathing techniques, meditation, mantras, and ethics. To date, only a few studies have tried to dismantle the effects of each of these components and their combinations. To fill this gap, we examined the incremental effects of ethical education and physical Hatha yoga on mantra meditation using a single-case multiple-baseline design. This study was part of a project evaluating the new mind–body program Meditation-Based Lifestyle Modification. Fifty-seven healthy participants from the community with no regular yoga or meditation practice were randomly assigned to three baselines (7, 14, and 21 days) and four conditions using a random number generator. The conditions were mantra meditation alone (MA), mantra meditation plus physical yoga (MY), mantra meditation plus ethical education (ME), and mantra meditation plus yoga and ethical education (MYE). All the interventions lasted for 8 weeks and were run consecutively according to baseline length. During the baseline and treatment phases, participants received daily questionnaires measuring their well-being (WHO-5 Well-Being Index), stress (Perceived Stress Scale), and subjective experiences. Forty-two participants completed the treatment and were entered in the analyses. We analyzed our data using visual inspection, effect size estimation (Tau-U), and multilevel modeling. Almost all participants showed a longitudinal increase in well-being. Regarding between-group differences, participants who received ethical education exhibited the largest increases in well-being (Tau U = 0.30/0.23 for ME/MYE), followed by participants in the MY condition (Tau U = 0.12). Conversely, participants in the MA condition showed no change (Tau U = 0.07). There was a longitudinal tendency for the combined treatments to decrease stress. This tendency was strongest in the MY condition (Tau U = 0.40) and reversed in the MA condition (Tau U = 0.17).These results emphasize the incremental and differential effects of practicing meditation in combination with other practices from the eightfold yoga path. This approach is valuable for better understanding the multifaceted practice of yoga.